Sediment dispersal along northern Israel coast during the early Holocene: Geological and archaeological evidence - Stanley, D. J.; Galili, E. (Marine Geology, 1996)
geological and archaeological study of finds at Atlit-Yam, a Pre-Pottery Neolithic settlement submerged off the Carmel coast of northern Israel, provides new information on sediment provenance and dispersal in the southern Levant. Clay mineral analyses of mud-rich samples collected in a water well (ca. 8100-7550 yrs B.P.) at this site are useful for determining the early Holocene circulation pattern along this margin. Analyses record the predominance of fluvial sediment from proximal Carmel highland sources to the east, as indicated by illite, and of marine sediment from the north and northeast, as indicated by kaolinite. This north-to-south coastal transport is in marked contrast to the present south-to-north dispersal pattern where smectite-rich Nile material is derived from distal sources and carried hundreds of kilometers to the Carmel margin. The interpreted coastal circulation pattern indicates that although the modern Nile delta, major source of sediment in the eastern Mediterranean, had begun to form about 8000-7500 yrs ago, it had not yet begun to supply substantial amounts of sediment to as far north as the Carmel coast by the time the water well was abandoned. The Atlit-Yam site serves as a unique geochronologic gauge valuable for interpreting climatic, oceanographic and sedimentologic conditions in the SE Mediterranean which, as recently as 7500 yrs ago, were markedly different than those prevailing at present.
Ue849Times Cited:13Cited References Count:30